Enteropathic arthritis. - Holden, W; Orchard, T; Wordsworth, P (2003)
Enteropathic arthritis is a form of arthritis associated with the chronic inflammatory bowel diseases, ulcerative colitis, and Crohn's disease. This form of arthritis is classified as one of the group of seronegative spondyloarthropathies, which also includes psoriatic arthritis, reactive arthritis, and idiopathic ankylosing spondylitis. Joint involvement also occurs with other gastrointestinal diseases such as Whipple's disease, celiac disease, and following intestinal bypass surgery for morbid obesity. In these conditions, abnormal bowel permeability and immunologic and genetic influences are probably involved in the pathogenesis of the joint disease, although the exact mechanisms remain uncertain.